Upaya Meningkatkan Keberhasilan Usaha Industri melalui Implementasi Konsep Pemasaran - Siti Noor Hidayati (Jurnal Maksipreneur, 2011)
These days corporate world faces tight competition, so that marketing function in company become of vital importance. One of the strategies to interrogate that by using marketing concept. Implementation of marketing concept that is market orientation, consist of customer orientation, competitor orientation and inter function coordination, and also competitive advantage will improve efficacy of industrial effort. Research on 50 respondent of batik industry in Yogyakarta showed that customer orientation, competitor orientation, inter function coordination and competitive advantage proven improve efficacy of industrial effort by significant, both all variable (F-test) and also partially (t-test). Result of multiple correlation very strong (R = 0.92), most dominant variable is customer orientation (highest r2).